PRÁTICAS PEDAGÓGICAS ANTIRRACISTAS NA EDUCAÇÃO INFANTIL: UMA EXPERIÊNCIA EM SERRA/ES - Oliveira, Ednalva Rodrigues de (2022)
The present study aimed to promote the discussion and confrontation of racism among children through the promotion of pedagogical practices. The development of the research started from the dialogue with the children and the interaction, with the help of toys, games and storytelling with African and Afro-Brazilian literature and with the autonomy to talk, question, recognize, exchange knowledge and experiences about the racial aspects. In this context, theorists and researchers who deal with issues related to the theme were reviewed, such as: Eliane dos Santos Cavalleiro (2000, 2001), Nilma Lino Gomes (2002, 2003, 2007, 2009, 2016, 2017, 2019 ) and Kabengele Munanga (2005, 2016, 2020) on the Education of Ethnic-Racial Relations; Stuart Hall (2014, 2016) on Identities and Social Representation; Manuel Jacinto Sarmento (2005, 2007), Lucimar Rosa Dias (2017, 2021), Anete Abramowicz and Fabiana de Oliveira (2012) on Childhood Studies; Paulo Freire, from a liberating and dialogical education (1987, 1992, 2014). In this sense, qualitative research was adopted, which, from the perspective of action research, enabled the teacher-researcher to engage in the elaboration of anti-racist proposals in partnership with children. For the records of the collected data, field notebooks, filming and photographs were used. The investigations took place on the physical spaces of the institution, the documents that govern the organization of the institution and the pedagogical resources that make up the institution from the perspective of ethnic-racial diversity, as well as playful interactions, in order to listen to what the children had to say. on racial issues. The locus of the research was the Municipal Center for Early Childhood Education (CMEI) located in the municipality of Serra, in the State of Espírito Santo. Starting from the reflection that a portion of the children who attend the early childhood education institution are black, the importance of pedagogical proposals that value their aesthetics is emphasized, as the cultural artifacts presented to them in this age group can compromise their psychological and social development. The children's contact with the playful materials provided moments of joy and racial belonging. In this age group, they demonstrate having a conception of identifying their color by claiming to be black, black or white during the activities. The research contributed to my professional and subjective training as a teacher and black woman, inspiring the continuity of the research on the theme Education for Ethnic-Racial Relations in the area of education. I emphasize that the racial issue requires other perspectives of education that involve the entire school community, including black and white teachers, in the fight against racism.